No child left behind? : the politics and practice of school accountability - Peterson, Paul E.; West, Martin R. (Brookings Institution Press, 2003)
Annotation "The first scholarly assessment of the new legislation, No Child Left Behind? breaks new ground in the ongoing debate over accountability. Contributors examine the law's origins, the political and social forces that gave it shape, the potential issues that will surface with its implementation, and finally, the law's likely consequences for American education."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved